The Relationship Between Diet Compliance And Blood Sugar Levels In Diabetes Mellitus Patients At The Internal Medicine Poly RSUD Ploso Jombang - Enny Puspita; Roni Setyawan; Moh. Syamsul Maarif (Sean Institute, 2024)
Increased blood sugar levels in diabetes mellitus sufferers can be caused by several factors, including lack of blood sugar control, unbalanced diet, lack of physical activity, and insulin resistance. This study aims to determine the relationship between dietary compliance and blood sugar levels in diabetes mellitus sufferers at the Internal Medicine Clinic, Ploso Hospital, Jombang. This research used a correlational analytical design with an average population of 201 people per month using a purposive sampling technique to obtain a sample of 32 people with research measuring tools using questionnaires and GCU. The results of this study showed that the majority of diabetes mellitus patients did not adhere to their diet, 20 people (62.5%), and almost half of diabetes mellitus patients had abnormal blood sugar levels, 22 people (68.8%). The results of the Spearman rank test showed a value of 0.000 (<0.05), meaning that there was a relationship between diet compliance and blood sugar levels in diabetes mellitus sufferers at the Internal Medicine Clinic, Ploso Hospital, Jombang Regency. Sufferers who adhere to the diet plan recommended by the medical team tend to have better blood sugar control. Adherence to a diabetes diet, which includes choosing foods that are low in sugar and carbohydrates, and controlled portions, plays a crucial role in the management of diabetes mellitus.